PENGARUH AKTIVITAS MENGHAFAL AL-QURAN TERHADAP KINERJA PEGAWAI (Studi Kasus Pada Rumah Tahfizh Darus Syifaâ€™ RSI Sultan Agung) - Samsudin, Samsudin; Makhshun, Toha; Farhan, Moh (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2020)
ABSTRACTOne of the efforts made to build the performance of human resources management is to foster work motivation through the development of Human Resources into qualified, professional and devoted personnel. Employee performance is very important in determining company performance. Sultan Agung Hospital is the first health service provider institution to organize the tahfizh al-Qur'an learning program for employees held at the House of Tahfizh Darus Syifa '. Preliminary study results at RSI Sultan Agung show that employees involved in memorizing the Koran have a good performance. This can be proven through the achievement of employee Key Performance Indicators (KPI), DP3 (List of Work Implementation Ratings) and work achievements. The approach used in this research is quantitative with experimental and survey methods. Data collection techniques were carried out through the collection of performance documents and questionnaires for 38 employees as samples of research objects. The analysis technique used is path analysis (descriptive and inferential statistical analysis).Â Keywords : Tahfizh al-Quran, Employee Performance